Dietary supplementation of quercetin nanoparticles enhances the growth performance hematological and immunological responses and resistance to Aeromonas hydrophila infection in Nile tilapia (Oreochromis niloticus) exposed to silver nanoparticles toxicity - Eman Ismail El behery; Chuntian Zheng; Mayada R. Farag; Mahmoud Alagawany; Seham El-Kassas; Mahmoud M. Azzam; Alessandro Di Cerbo; Eman Wagih (Aquaculture Reports, 2023)
The wide incorporation of silver nanoparticles (AgNPs) in aquaculture could result in releasing of these particles into the environment with environmental impacts and health hazards. Thus, this study aimed to investigate the impacts of the dietary supplementation of quercetin nanoparticles (QNPs) on Nile tilapia (Oreochromis niloticus) growth, antioxidants, and immunity besides its susceptibility to the infection with Aeromonas hydrophila with or without the aqueous exposure to AgNPs. First, the 96-h LC50 value for AgNPs in O. niloticus wa estimated to be 19.81 mg/L (the 1/10th of the 96 h LC50 of AgNPs = 1.98 mg/L). Then a total of 240 Nile tilapias (40.00 ± 0.45 g) were randomly distributed into 4 groups (each group contains 60 fish in 3 replicates of 20 fish). The 1st group (control) was fed on a basal diet without QNPs and AgNPs. The 2nd group (QNPs) received the basal diet supplemented with QNPs (400 mg/kg), the 3rd group (AgNPs) was exposed to 1/10th 96-h LC50 of AgNPs (1.98 mg/L) and fed on QNPs free diet, while the 4th group (AgNPs+ QNPs) was exposed to AgNPs (1.98 mg/L) and co-supplemented with QNPs (400 mg/kg). Besides, AgNPs resulted in marked elevation in the serum myeloperoxidase (MPO) 8-hydroxy-2-deoxyguanosine (8-OHdG) contents, and declines in lysozyme activity and the levels of nitric oxide (NO) and immunoglobulins (IgM and IgG) in the exposed fish (AgNPs group). These effects were accompanied with significant downregulation in the relative mRNA expressions of SOD, CAT, and GSH and upregulation in the expressions of INF-γ, TNF-α, and Il-1β. Feeding QNPs-enriched diet, alone or combined with AgNPs exposure, conversed most of these effects and restored some to the control levels. AgNPs exposure increased mortalities, lowered survival rates and altered Nile tilapia’s resistance to A. hydrophila infection in the AgNPs exposed fish, whereas co-supplementation with QNPs enhanced their resistance with less mortalities. In summary, the reported immunomodulation, and protective properties of QNPs dietary supplementation, strengthen its applicability as an effective and promising feed supplement to alleviate the AgNPs associated toxicity in fish.